Aplikasi Budidaya Itik Petelur Berbahan Pakan Lokal pada Kelompok Tani Nyiur Melambai - Untu, Sonny Denny; Palandi, Reky Royke; Rumondor, Fadly Steven Jefry; Montolalu, Friska Mery; Kanter, Jabes; Karauwan, Ferdy; Korua, Sammy Rommy Novie (Universitas Klabat, 2024)
This service aims to help the Nyiur Melambai Farmers Group in Tomohon City in increasing the productivity of laying ducks through the application of locally made feed. The main problems faced by partners are the high price of commercial feed, low knowledge in making alternative feed, and suboptimal business management. The solutions implemented include training in processing feed from local ingredients, introduction to appropriate technology, and cage renovation. The results of this activity show an increase in feed production, a reduction in feed costs, and an increase in the capacity of partners in business management. This service contributes to increasing partner income and strengthening the sustainability of the laying duck business.